University Students’ Perception on TOEFL as a Graduation Requirement: A Case in UIN Syarif Hidayatullah Jakarta - Alek; Muhammad Farkhan; Vera Nurlia; Gashella Makhpirokh Haucsa (ELITE Association Indonesia, 2019)
This survey study aims to reveal the students’ perceptions towards Test of English as a Foreign Language (TOEFL) is one of graduation requirement policy in Syarif Hidayatullah State Islamic University, Jakarta. This study also investigates what challenges and gains the students get from taking the test. Forty students from different major and status (graduated and not graduated yet) in Syarif Hidayatullah State Islamic University, Jakarta, were chosen as the participants. The data was gathered through questionnaires and interviews. There are seventeen questionnaire items regarding students’ perception of the policy were given to the participants. Moreover, the interview was also conducted to support the result of the data collected by asking some of the participants’ opinion related to the implementation of the policy of TOEFL as one of the graduation requirements. The research findings showed that nearly all participants supported the policy of TOEFL as a graduation requirement. It indicated that most of the participants considered TOEFL as an essential requirement for graduation as this policy allowed them to enhance their English proficiency and motivate them to learn English. Furthermore, from the findings, it can also be seen that the challenges and gains encountered by the students are varied.